Activation of glial glutamate transporter via MAPK p38 prevents enhanced and long-lasting non-evoked resting pain after surgical incision in rats - Reichl, Sylvia; Jonas, Robin (Neuropharmacology, 2016)
Pain after surgery has recently become a major issue not only due to lack of treatment success in the acute phase; even more alarming is the large number of patients developing prolonged pain after surgery. Because spinal glutamate as well as spinal glia plays a major role in acute incisional pain, we investigated the role of the spinal glial glutamate transporters (GT), GLAST, GLT-1, for acute and prolonged pain and hyperalgesia caused by an incision. Spinal administration of the GT-inhibitor DL-TBOA increased non-evoked pain but not evoked pain behavior (hyperalgesia) up to 2 weeks after incision. In accordance, spinal GLAST (and to a lesser degree GLT-1) were upregulated after incision for several days. Long-term incision induced GT upregulation was prevented by long-lasting p38-inhibitor administration but not by long-lasting ERK1/2-inhibition after incision. In accordance, daily treatment with the p38-inhibitor (but not the ERK1/2 inhibitor) prolonged non-evoked but not evoked pain behavior after incision. In electrophysiological experiments, spontaneous activity of high threshold (HT) (but not wide dynamic range (WDR)) neurons known to transmit incision induced non-evoked pain was increased after prolonged treatment with the p38-inhibitor. In conclusion, our findings indicate a new spinal pathway by which non-evoked pain behavior after incision is modulated. The pathway is modality (non-evoked pain) and neuron (HT) specific and disturbance contributes to prolonged long-term pain after surgical incision. This may have therapeutic implications for the treatment of acute and - even more relevant - for prevention of chronic pain after surgery in patients.